Randomized Study of the Effect of Initial Ropivacaine Dosage during Continuous Popliteal Nerve Blocks on Rebound Pain in Foot and Ankle Surgery. Issue 4 (16th October 2019) - Rogero, Ryan; McDonald, Elizabeth; Raikin, Steven M.; Fuchs, Daniel; Shakked, Rachel J.; Voskeridjian, Armen
Category: Basic Sciences/Biologics, Anesthesia/Pain Control Introduction/Purpose: Rebound pain, the quantifiable difference in pain experienced after nerve block resolution, can be a substantial component of postoperative pain, opioid intake, sleep disturbances, and patient satisfaction. A relatively higher concentration initial local anesthetic bolus may contribute to this phenomenon, as the transition from an entirely numb and painless limb to a partially numb limb may lead to greater perceived pain following block resolution. In contrast, patients experiencing some level of background pain immediately following surgery due to a lower concentration initial bolus may have less perceived pain after block resolution. The purpose of this study is to evaluate the influence of the initial local anesthetic concentration in continuous popliteal nerve blocks on rebound pain and other postoperative variables in foot and ankle surgery. Methods: Following IRB approval, patients undergoing outpatient foot and ankle procedures requiring continuous popliteal nerve blocks under the care of a single fellowship-trained foot & ankle surgeon were identified. Subjects were randomized and blinded to either the standard (0.5%) or low-dose (0.2%) initial ropivacaine bolus, both being followed by a continuous 0.2% ropivacaine catheter infusion. From postoperative days 1 to 7, subjects recorded their hourly visual analog scale (VAS) pain level out of 100, perceived pain relief from the block, and satisfaction with pain control, as well as daily narcotic intake and other postoperative side effects, through an electronic survey. Rebound pain was scored according to a published method by subtracting the lowest VAS pain score during the 12 hours prior to the subject's determination of block resolution from the highest VAS pain score in the 12 hours after resolution. 69 subjects completed the study. Outcomes were compared using Student's t-tests. Results: Thirty-four subjects received a standard initial 0.5% ropivacaine bolus, while 35 received a 0.2% bolus. Chi-square testing and t-tests revealed no difference in any preoperative patient variables or procedural type/location between groups. Subjects receiving the lower 0.2% ropivacaine bolus had a lower rebound pain score (47.6) than those receiving the standard ropivacaine bolus (51.0), though not significantly (p=.679). The group receiving the lower concentration bolus only reported a higher mean VAS pain at 72 hours following surgery (39.6 vs. 25.7, p=.044) and more pain interference with sleep (p=.015) on postoperative day 5. The groups did not differ significantly (p>.05) on any day in terms of morphine equivalent units (MEUs) consumed, satisfaction with pain control, nausea, constipation, or nerve-related symptoms of tingling, numbness, and hypersensitivity. Conclusion: The utilization of a lower concentration initial local anesthetic bolus in continuous peripheral nerve blocks in foot and ankle surgery did not significantly lower rebound pain, but provided similar postoperative pain control as a standard local anesthestic bolus concentration. Further investigation with larger cohorts is needed to further optimize local anesthetic concentration in continuous nerve blocks in order to limit postoperative pain, side effects, and opioid intake following foot and ankle surgery.